From rote to reflective: Integrating ChatGPT to transform learning outcomes in Cambodian education - Huot, Sovanna; Loch, Sovanna (International Journal of Language and Literary Studies, 2025)
Cambodia’s education system has long been shaped by rote memorization, hierarchical classroom structures, and examination-focused curricula, practices that often inhibit the development of critical and reflective thinking. This review explores how ChatGPT, a generative artificial intelligence (AI) tool developed by OpenAI, can serve as a catalyst for shifting Cambodian learning paradigms from repetition-based instruction to more reflective, student-centred engagement. Drawing on a narrative and thematic integrative review of literature published between 2022 and 2025, the study synthesizes empirical and conceptual findings from global and regional sources, aligned with Cambodian policy frameworks. Key themes include ChatGPT’s impact on conceptual understanding, learner motivation, and metacognitive development. The findings suggest that while ChatGPT can enhance student learning when used for dialogue, clarification, and feedback, its success depends heavily on pedagogical design, teacher facilitation, and ethical integration. Major challenges include infrastructure gaps, digital literacy limitations, linguistic constraints, and cultural norms around teacher authority. The paper concludes with actionable recommendations for policymakers, educators, and researchers, including the development of Khmer-language AI tools, integration of AI literacy into national curricula, and the need for pilot studies and ASEAN-level comparative research. Ultimately, the review affirms that with inclusive planning and sustained investment, ChatGPT can support Cambodia’s transition toward a more reflective, equitable, and future-oriented education system.